The Critical Role and Therapeutic Potential of the CXCR Family in Skin Diseases - Jin Xu; Chaoyi Wang; Yundong Xu; Bingchen Li; Jianzhou Ye (Frontiers in Bioscience-Landmark)
The C-X-C chemokine receptors (CXCR) chemokine receptor family, consisting of seven primary members (CXCR1–CXCR7), is crucial in regulating immune cell recruitment, angiogenesis, cellular proliferation, and maintaining skin homeostasis and immune functions. This review evaluates the expression and roles of CXCR receptors across a range of skin cells, including keratinocytes, fibroblasts, endothelial cells, melanocytes, and various immune cells such as T cells, dendritic cells, and macrophages. Aberrations in CXCR signaling have been associated with a variety of skin disorders, such as psoriasis, atopic dermatitis, acne, and skin cancers. Despite significant advancements in the field, several critical questions persist. These include the differential effects of CXCR signaling in distinct skin pathologies and the intricate interactions between CXCR receptors and their ligands within diverse skin microenvironments. Moreover, the therapeutic targeting of the CXCR family remains unresolved, necessitating further research into its long-term efficacy and possible adverse effects. Future investigations should prioritize these critical issues to develop more effective therapeutic strategies for managing skin diseases, ultimately improving patient outcomes.